Strontium-substituted hydroxyapatite nanoparticles associated with type I-collagen enhances the obliteration of dentinal tubules and the mineralization by human dental pulp stem cells - Macedo, Jeferson Mateus Moussa; Kazmirczak, Paula Consul; Hayann, Larwsk; Dotta, Tatiane Cristina; Cassiano, Ana Flávia Balestrero [UNESP]; Palma-Dibb, Regina Guenka; Ciancaglini, Pietro; Blasida, Alma; Elizaur, Concepcion; Catirse, Benitez; Faria, Gisele [UNESP]; Ramos, Ana Paula (Springer Nature, 2025)
Dental hypersensitivity is related to dentin exposure due to erosion of mineralized tissue. Although several desensitizing materials have been synthesized, this condition still affects almost half part the population worldwide. In this study, we have prepared biomimetic composites based on type-I collagen and strontium-substituted calcium phosphates nanoparticles synthesized replacing Ca2+ by Sr2+ in different extent and investigated their potential use as restorative materials, mainly evaluating their ability to obliterate tubules and to restore the permeability of healthy dentin. The action of the isolated nanoparticles as a remineralizing agent was also investigated. The composites were applied on demineralized dentin discs followed by acid challenges. The dentin tubules obliteration was evaluated by Fourier transform infrared spectroscopy (FTIR), surface free energy (SFE), scanning electron microscopy (SEM), confocal microscopy, energy dispersive X-ray spectrometry (EDS), microhardness, and dentin permeability, and the effects of nanoparticles on human dental pulp stem cells (hDPSC), including their remineralization ability, were evaluated by cell viability assay (MTT), formation of mineralized nodules, and the expression of osteogenic markers by RT-qPCR. The results showed that the composites efficiently obliterate dentin tubules, restoring the permeability and physicochemical characteristics of the healthy dentin, where type-I collagen was shown to be fundamental for adhesion of the nanoparticles. From the cellular point-of-view, the presence of Sr2+ in the nanoparticles was not cytotoxic and activated tissue-nonspecific alkaline phosphatase (TNAP) activity also increasing the formation of mineralized nodules. Finally, the gene expression results indicated that nanoparticles induced osteogenic differentiation of hDPSC. These findings suggest that composites may be great candidates as desensitizing agents.
Keywords: Adhesion; Collagen; Hydroxyapatite; Mineralization; Osteogenic differentiation; Strontium